Cost Of Illness, Health-Related Quality Of Life And Costeffectiveness Analysis Of Pharmacistled Lifestyle Intervention Among Diabetes Population In Pakistan - Daoud, Butt Muhammad (2024)
Diabetes mellitus is a growing public health concern in Pakistan, imposing a substantial economic burden and negatively affected individuals’ health. Pharmacistled lifestyle interventions may manage diabetes, but their cost-effectiveness in Pakistan is unknown. This study aims to evaluates Diabetes cost of Illness, HRQoL, and pharmacist-led lifestyle treatment cost-effectiveness. Over 12 months, a socially extensive economic analysis was done. The cost of illness study covered direct, nonmedical, and indirect diabetes management costs. The societal cost of illness was calculated. The quantitative study assessed HRQoL with the EQ-5D-5L and diabetesspecific distress with the DAI-10. Medication behavior and self-management were examined using the MDKT and DSMQ. A randomized controlled trial examined pharmacist-led diabetes education. To calculate incremental cost-effectiveness, a decision-analytic model compared pharmacist-led lifestyle changes to standard treatment. Pakistani Diabetes Outpatient Clinics provided 1,839 diabetics for the study. Three districts were selected from each province, afterwards from these districts only metropolitan cities were selected, clustered sampling approach was used and 150 participants were included from each districts. In Phase 1 over 1,839 Pakistani outpatient clinic diabetic patients were investigated. Alarmingly, several patients had uncontrolled blood sugar, requiring improved treatment. The annual total cost of diabetes care was USD 740.1. The cost covered direct, non-medical, and indirect diabetes management costs.